2016
DOI: 10.1016/j.actatropica.2016.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Deltamethrin-mediated survival, behavior, and oenocyte morphology of insecticide-susceptible and resistant yellow fever mosquitos (Aedes aegypti)

Abstract: Insecticide use is the prevailing control tactic for the mosquito Aedes aegypti, a vector of several human viruses, which leads to ever-increasing problems of insecticide resistance in populations of this insect pest species. The underlying mechanisms of insecticide resistance may be linked to the metabolism of insecticides by various cells, including oenocytes. Oenocytes are ectodermal cells responsible for lipid metabolism and detoxification. The goal of this study was to evaluate the sublethal effects of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…However, based on our results for deltamethrin toxicity, such conclusions should be analyzed with caution. Whereas the susceptibility of B. tarsalis to deltamethrin (LC50 ¼ 4.0 ng a.i./L) was similar to that of other backswimmer species (e.g., Anisops sardeu) in the subfamily Anisopinae [30], the deltamethrin LC50 for M. bentoi was several fold higher than that for B. tarsalis and A. sardeu, which reinforces the idea that differences in the toxicodynamics of insecticide poisoning, or in physiological and biochemical peculiarities associated with each aquatic insect species, regulate the susceptibilities of these organisms to insecticide exposure [1,4,14,15,26].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…However, based on our results for deltamethrin toxicity, such conclusions should be analyzed with caution. Whereas the susceptibility of B. tarsalis to deltamethrin (LC50 ¼ 4.0 ng a.i./L) was similar to that of other backswimmer species (e.g., Anisops sardeu) in the subfamily Anisopinae [30], the deltamethrin LC50 for M. bentoi was several fold higher than that for B. tarsalis and A. sardeu, which reinforces the idea that differences in the toxicodynamics of insecticide poisoning, or in physiological and biochemical peculiarities associated with each aquatic insect species, regulate the susceptibilities of these organisms to insecticide exposure [1,4,14,15,26].…”
Section: Discussionsupporting
confidence: 75%
“…The susceptibility of aquatic insects to insecticides is related to physiological and behavioral constraints associated with aquatic ecosystems [1,15,20,26,27]. In the present study we demonstrated that 2 phylogenetically related backswimmer species (B. tarsalis and M. bentoi) had different susceptibilities to deltamethrin, which also had effects on individual swimming activities.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Populations were reared following the procedure described in Marriel et al . (2016) . The larvae of A. aegypti populations were kept in plastic trails (6 L) with 5 L of water (chlorine free) and they were fed with animal rations.…”
Section: Methodsmentioning
confidence: 99%